Enhancing Earth and Environmental Science Undergraduate Students' Perception of Geographic Information Systems through Short Clips - Irene DeFelipe; Paula Sofía Jerez-Longres; Irene Pérez-Cáceres; Pablo Valenzuela; Jorge Pedro Galve; Sonia Rodríguez-Ruano; Zaida Ortega; Luna Adrados; José Manuel Bernabé; José Crespo; Romina Marisel Montes; Lola Pereira; et al. (MDPI AG, 2024)
Geographic Information Systems (GISs) cover a wide range of Earth and environmental science disciplines that have become essential for spatial data management, easing the digital transformation needs of our society. Despite the usefulness of GISs, they remain underutilised in academia, and many students do not understand the possibilities that these tools offer. To familiarise university students with the potential of GISs, we designed 11 short clips (less than 5 min long) recorded by Earth scientists with diverse backgrounds who shared their work experience with GISs to solve real-world problems. Through these short clips, we emphasised not only the multidisciplinary uses of GISs but also provided professional references for undergraduate students, including societal aspects such as gender equality, national and international mobility, private-to-public-sector transitioning, and different family circumstances. As a result, the students expressed their interest in the applications of GISs, many of which were completely new to them, highlighting the potential of GISs in terms of entrepreneurship and their usefulness in mitigating global change. Thus, we were able to transfer knowledge from research to university education and foster spatial data management skills in Earth science.